2018
DOI: 10.1038/s42004-018-0082-3
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput first-principles-calculations based estimation of lithium ion storage in monolayer rhenium disulfide

Abstract: Two-dimensional materials are promising candidates for lithium ion battery anodes due to their large surface to volume ratio. The distorted T′ phase of the rhenium disulfide crystal makes the study of lithium binding more complex than for other two-dimensional materials with symmetric crystal structures. Here we explore the lithium ion storage capacity of monolayer rhenium disulfide by first-principles based calculations. We employ hardwareaccelerator-assisted high-throughput calculations, using a van der Waal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…have been implemented here. The AIRSS Shake & Relax algorithm and its highly parallel masterslave implementation are similar to that of our previous works 12,13 . To accelerate the DFT calculations, hardware-accelerators have been employed extensively.…”
Section: S41mentioning
confidence: 55%
“…have been implemented here. The AIRSS Shake & Relax algorithm and its highly parallel masterslave implementation are similar to that of our previous works 12,13 . To accelerate the DFT calculations, hardware-accelerators have been employed extensively.…”
Section: S41mentioning
confidence: 55%
“…However, the calculated specific capacities are known to be drastically overestimated when compared to empirical findings. , One reason for this could be using the “uniform adsorption” model in most of these studies. Recently, multiple high-throughput structure-searching-based computational studies have demonstrated the “uniform adsorption” model’s limits while predicting the most stable cation-adsorbed phase and the specific capacity. , Another possible reason is that these studies cannot incorporate the nonideal effects of multiple charging–discharging cycles, such as bond breaking and formation, phase change of adsorbent, irreversible Li adsorption, electroplating, and so on. In such cases, the uniform-adsorption-predicted theoretical specific capacity might match experimental values for the first few cycles, but rapid capacity fading would soon reduce the quantity to a much lower reversible “effective capacity” which we have previously demonstrated for monolayer ReS 2 . , …”
mentioning
confidence: 99%
“…Such phase change (2H to 1T) with lithiation has already been reported for monolayer MoS 2 , , whereas in-situ and ex-situ microscopy studies have revealed semireversible bond cleavage and Li 2 S and other compound formation in the case of MoS 2 and NbS 2 electrodes. Traditional computational studies lack the machinery to predict and explain such phenomena. Our recent top-down (starting with a known crystal structure of the host and adding Li ions to its surface) structure-searching-based study has been partially successful for ReS 2 and MoS 2 in this regard . Calculation of the formation energy of lithiated electrode compounds as a function of Li concentration and subsequent construction of the convex hull (i.e., thermodynamic assessment of the Li-electrode composition space) has become a popular tool to predict the globally most stable lithiated phases and concurrently the figure of merits. ,, Forcefully charging the electrode beyond the global energy minimum can induce irreversible changes that could ultimately result in significant capacity fading and even disintegration of the electrode material.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This PBE-D3 level of DFT has been validated for several molecular systems, including DFT-MD simulations of metal-organics and Li-ion battery interfaces in particular. 27,28,[48][49][50] The energy cutoff for the plane-wave basis expansion was chosen at 500 eV, which was verified to provide converged forces by a test calculation at 600 eV. For the bulk Brillouin zone integration, a Γ-centered k-point mesh was used in all DFT-MD simulations within the supercell.…”
mentioning
confidence: 99%